Current pathophysiological concepts in cerebral small vessel disease - Rincon, Fred; Wright, Clinton (Frontiers in Aging Neuroscience, 2014)
The association between cerebral small vessel disease (SVD) – in the form of white matter lesions, infarctions, and hemorrhages – with vascular cognitive impairment (VCI), has mostly been deduced from observational studies. Pathological conditions affecting the small vessels of the brain and leading to SVD have suggested plausible molecular mechanisms involved in vascular damage and their impact on brain function. However, much still needs to be clarified in understanding the pathophysiology of VCI, the role of neurodegenerative processes such as Alzheimer’s disease, and the impact of aging itself. In addition, both genetic predispositions and environmental exposures may potentiate the development of SVD and interact with normal aging to impact cognitive function and require further study. Advances in technology, in the analysis of genetic and epigenetic data, neuroimaging such as magnetic resonance imaging, and new biomarkers will help to clarify the complex factors leading to SVD and the expression of VCI.